Australian Prison Libraries: A Study of Existing Knowledge and Recent Findings. Issue 4 (8th November 2017) - Garner, Jane
Abstract: This paper reviews the literature relating to libraries in prisons and introduces findings from a recent study that explores the lived experience of using Australian prison libraries. The paper identifies literature regarding the history of libraries in prisons, both in Australia and elsewhere, and then studies contemporary prison libraries and the standards and documents that guide their management and practices. One of the main roles of incarceration is the reform of the individual. As the role of education in this process is considered to be crucial, the educational and broader information needs of prisoners are discussed, along with the role prison libraries can play in supporting prisoners to satisfy these needs. This discussion is followed by a study of the nature of existing research and publications relating to prison libraries. The lack of understanding of the prison library user experience, particularly within the Australian context, is identified. A recent doctoral study designed to address this lack of knowledge is introduced, and the paper ends with the identification of five themes identified by that study that describe the experience of using Australian prison libraries.